Carotid Body Tumor: Clinical Features - Kaygusuz, Irfan; Karlidag, Turgut; Keles, Erol; Yalcin, Sinasi; Yuksel, Koray (Lippincott Williams & Wilkins, 2015)
Although carotid body tumor (CBT) is a rare neoplasm, it should always be considered in differential diagnosis of lateral neck masses. We shared the 10 years of CBT experience in our clinic and started a discussion on CBT with literature support. A total of 21 patients with CBT diagnosis in Firat University Hospital, Otorhinolaryngology Clinic, participated in the study. Patients were evaluated based on demographical data and particularities of the tumor. Participant patients were 19 women and 2 men, and their ages were between 21 and 79 (mean age 54.06 +/- 12.48). The most frequent reason for the patients to apply to the hospital was painless swelling in the neck (76.2%). Tumor was located in the right side of the neck in 10 patients (47.6%), and in the left side of the neck in 11 (52.4%). Twenty patients (95.2%) had undergone computerized tomography angiography. Surgical treatment was applied to 19 patients (90.5%) and the tumor was totally excised. According to Shamblin classification, 15 of the tumors of these patients were class II (78.9%) and 4 were class III (21.1%). In 1 patient (5.3%), postoperative contusion infection that recovered after medical treatment was observed; in 2 patients (10.5%), n. vagus injury was observed because of tumor's pervasion of n. vagus; and in 1 of these patients vocal cord paralysis was developed and this patient was later taken into thyroplasty surgery. Two patients (10.5%) suffered n. hypoglossus injury, 1 of these recovered within 3 months postoperative and the other developed n. hypoglossus palsy. The size and extension of the tumor should be determined by pre-operative imaging for the correct planning of surgical procedure. It should be taken into consideration that despite advanced surgical techniques, the rate of postoperative cranial nerve damage is still high.
Keywords: Carotid body tumor; chemodectoma; lateral neck mass